SATORI : a support tool for young adults with autism to self-manage stress and anxiety - Espinosa A., Marcela; Escobedo Bravo, Lizbeth Olivia (My University, 2021)
Individuals with autism may experience higher levels of stress and anxiety for longer periods than neurotypical individuals. Traditional techniques to provide stress relief and anxiety management include support that reminds people how to face stressful situations. In this research we present the results of a qualitative study that led to the design of SATORI, a support tool composed of three interfaces to help young adults with autism manage autonomously the anxiety caused by stressful situations from their daily life. We close discussing directions for future work.
Keywords: Young adults; Autism; Stress; Anxiety; Campus Tijuana